The effect of the graded bilayer design on the strain depth profiles and microstructure of Cu/W nano-multilayers. (1st November 2021) - Druzhinin, A.V.; Lorenzin, G.; Ariosa, D.; Siol, S.; Straumal, B.B.; Janczak-Rusch, J.; Jeurgens, L.P.H.; Cancellieri, C.
Graphical abstract: Highlights: The average stress is not representative of the real stress state in nano-multilayer. Strain depth profiles are derived and can be tailored by the Cu/W bilayers position. Design of the bilayer blocks arrangement is a tool to tailor the Cu surface outflow. In homogeneous nanocomposites are formed by thermal degradation of graded multilayers. Abstract: The properties and thermal stability of thin films and nano-multilayers (NMLs) are generally governed by the in-depth stress (strain) gradients rather than the average stress state. The effect of strain gradient variation in Cu/W NMLs on the thermal stability between 400 and 800 °C was investigated. The strain distribution in the NML stacks was varied by combining Cu/W bilayers with different Cu and W thicknesses of either 3 or 10 nm. A recently developed method based on in-plane grazing X-ray diffraction was adopted to extract the strain depth profiles. In addition, the evolution of the average stress in the Cu/W NMLs during growth was monitored by an in-situ wafer curvature technique. The mean residual stresses in Cu and W were found to be independent of the disposition of the different Cu/W bilayer substacks. On the contrary, the strain depth profile of the W nanolayers was found to strongly depend on the disposition of Cu/W bilayer substacks in the Cu/W NML, which resulted in different Cu outflow characteristics upon annealing. Moreover, application of different Cu/W bilayer units within the NML stack also provides an innovative pathway for producing Cu/W nanocomposites with graded thermal and mechanical properties.